THE USE OF CONTRAST IN SOME PLACES WHICH IS IN THE POETIC TEXT (Academia Science Repository, 2023)
This article reflects the use of contrast in a poetic text. Linguistic formation of contrast - the theory of contrasts, Contrast is expressed in various binary contrasts; phonetic, morphological, lexical, syntactic, stylistic, extra-textual and as one of the types of semantic-stylistic organization of the text.